Behavior of steel fiber reinforced concrete slab due to volume fraction of fiber - Shahidan, Shahiron (2009)
Generally, fibers are commonly used in engineering material. The characteristics and properties of fiber influence the properties concrete. This has been proven by the previous research. In this research steel fiber is used to study the behavior of reinforced concrete slab due to volume fraction of fiber subjected to flexural test based on computer simulation. The application of steel fiber reinforced concrete in civil construction is the most popular due to its improvement in resistance to cracking, fatigue, abrasion, impact, durability, and conventional reinforced concrete. In this investigation,finite element simulation will be used to analyze the normal reinforced concrete slab and steel fiber reinforced concrete slab due to diffrent percentage of volume fraction with 1%, 1.5%, 2%, 2.5% and 3%. Through this simulation, the loading is applied and analyzed by the increments of every 2 KN up to ultimate failure. The results are obtained from the computer programming simulation and being compared with published experimental results. The result of the analysis indicates that, by using and adding steel fiber into the conventional reinforced concrete, it will influence the ductility, toughness, energy absorption and strength of the concrete.